Intravenously Injected Pluripotent Stem Cell–derived Cells Form Fetomaternal Vasculature and Prevent Miscarriage in Mouse. (17th December 2020) - Daimon, Atsushi; Morihara, Hirofumi; Tomoda, Kiichiro; Morita, Natsuko; Koishi, Yoshinori; Kanki, Kazuyoshi; Ohmichi, Masahide; Asahi, Michio
Miscarriage is the most common complication of pregnancy, and about 1% of pregnant women suffer a recurrence. Using a widely used mouse miscarriage model, we previously showed that intravenous injection of bone marrow (BM)-derived endothelial progenitor cells (EPCs) may prevent miscarriage. However, preparing enough BM-derived EPCs to treat a patient might be problematic. Here, we demonstrated the generation of mouse pluripotent stem cells (PSCs), propagation of sufficient PSC-derived cells with endothelial potential (PSC-EPs), and intravenous injection of the PSC-EPs into the mouse miscarriage model. We found that the injection prevented miscarriage. Three-dimensional reconstruction images of the decidua after tissue cleaning revealed robust fetomaternal neovascularization induced by the PSC-EP injection. Additionally, the injected PSC-EPs directly formed spiral arteries. These findings suggest that intravenous injection of PSC-EPs could become a promising remedy for recurrent miscarriage.